THE INFLUENCE OF INFORMATION ON TRADING BEHAVIOR WITH PERSONALITY TRAITS AS MODERATION VARIABLE FOR STOCK TRADERS - Ronaldo Susanto; Mariana Ing Malelak (International Journal of Financial and Investment Studies (IJFIS), 2021)
The development of investment in Indonesia has increased rapidly over the past few years. One of the key factors affecting stock traders' trading behavior is information. Information that was previously difficult to obtain by investors became easily obtained due to technological developments. In addition to information, the characteristics of traders also influence their trading behavior. The population used in this study is the entire citizen of Surabaya, and the sample of this study is stock traders who have a minimum of 1-year trading experience. Data analysis is done by using Partial Least Square with Smart PLS 3.0. The result of this study is that information has a significant effect on trading behavior, while neuroticism, extraversion, openness, agreeableness, and conscientiousness do not moderate the effect of information on trading behavior significantly.